An Analysis of Investment for Hajj Funds from Islamic Law Perspective - Fahmi, Annas Syam Rizal (University of Darusssalam Gontor, 2017)
Being the largest Muslim country with some 250 million Muslims, Indonesia facesa huge demand from its citizens eager to perform Hajj and then it will impact to the hugeof funds to perform Hajj (Pilgrim). Initially, any surplus funds held by the Department ofReligion are supposed to be paid to the Islamic Community Perpetual Funds (DanaAbadi Umat). Currently, the government is now eyeing the country’s hajj (Muslimpilgrimage) fund as a potential source of infrastructure finance. By that araises somedebate whether the hajj funds can be used or no to finance Indonesia infrastructureproject. Therefore, the study intends to analyse the investment of hajj funds from Islamiclaw perspective. However, findings of the study are that the use of the hajj funds forinvestment is permissible in Islam with some condition such as the benefit gained from itis used for infrastructures abd facilities of hajj performance.